Pengaruh Minat dan Lingkungan Belajar Peserta Didik Terhadap Hasil Belajar Matematika - Nurdianti Nurdianti; Halidin Halidin; Farman Farman (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research objective used was to determine the effect of student interest and the learning environment on mathematics learning outcomes. This type of research is expo facto research. The sample in this study consisted of 47 students of class VIII SMP Negeri 1 Kolaka who were randomly selected by means of a proportional random sampling technique. The instrument used was a questionnaire of interest and the learning environment. The data analysis technique used in this research was descriptive statistical analysis techniques and inferential statistics with multiple regression analysis. Based on the results of data analysis, the following conclusions were obtained: (1) Learning interest, learning environment and learning outcomes of class students were in the high category. (2) There is a significant positive influence between interest in learning-on-learning outcomes in mathematics (3) There is a significant positive effect between the learning environment on learning outcomes in mathematics (4) There is a significant positive effect between interest in learning and the learning environment together on outcomes. learning mathematics class VIII students of SMP Negeri 1 Kolaka with the regression equation Y ? = 59.48 + 0.05X1 + 0.19 X2.